Lasiodiplodia iraniensis and Diaporthe spp. Are Associated with Twig Dieback and Fruit Stem-End Rot of Sweet Orange, Citrus sinensis, in Florida - Valeria Piattino; Dalia Aiello; Greta Dardani; Ilaria Martino; Mauricio Flores; Srđan G. Aćimović; Davide Spadaro; Giancarlo Polizzi; Vladimiro Guarnaccia (Horticulturae, 2024)
Florida ranks among the most important citrus growing regions in the USA. The present study investigates the occurrence, diversity, and pathogenicity of fungal species associated with symptomatic sweet orange (Citrus sinensis) cv. Valencia plants and fruit. The survey was conducted on twigs and fruit collected in Southwest Florida during 2022. Based on morphological and molecular characteristics, the identified isolates belonged to the species Lasiodiplodia iraniensis, Diaporthe pseudomangiferae, and Diaporthe ueckerae. The pathogenicity of representative isolates was evaluated on citrus fruit and plants. Lasiodiplodia iraniensis was the most virulent on fruit and plants, followed by Diaporthe pseudomangiferae. Diaporthe ueckerae had the lowest virulence on fruit, and it was not pathogenic to plants. In vitro tests were performed to assess the effect of temperature on mycelial radial growth. The optimum temperature of growth ranged from 26.0 to 28.4 °C for all the evaluated species, and L. iraniensis showed the fastest mycelial growth. This study represents the first report of L. iraniensis as a causal agent of tree dieback and fruit stem-end rot on C. sinensis worldwide. Moreover, D. pseudomangiferae and D. ueckerae are reported here for the first time in association with citrus diseases worldwide.